PP.LB03.04: CEREBRAL MICROVASCULAR RAREFACTION AND DYSFUNCTION ARE REVERSED BY SIMVASTATIN IN A MODEL OF PRIMARY HYPERTENSION. (June 2015) - Tibirica, E.; Estato, V.; Lessa, M.A.; Reis, P.; Castro-Faria, H.; Freitas, F.
Abstract : Objective: Statins are widely used in the treatment of dyslipidemia, which is usually associated with cardiovascular abnormalities including hypertension. Microvascular rarefaction and endothelial dysfunction are aggravating factors of hypertensive end-organ damage. Thus, this study was designed to investigate the acute effects of simvastatin (SIM) on cerebral microcirculation and endothelial function in spontaneously hypertensive rats (SHR). Design and method: Male Wistar normotensive rats (WKY) and SHR were divided into 3 groups of 6 animals each: WKY-CTL and SHR-CTL treated with 0.9% saline solution, and SHR+SIM treated with SIM (30 mg/kg/day) during 3 days by gavage. Systolic blood pressure (SBP) was measured by tail-cuff plethysmography. We investigated brain functional capillary density (FCD) and vascular reactivity using intravital fluorescence videomicroscopy after IV injection of FITC labeled dextran. We assessed endothelium-dependent vasodilator responses of cerebral arterioles induced by local administration of acetylcholine (Ach, 10-6 M). Vascular responses were expressed as percentage changes from the baseline arteriolar diameters. Values are means ± S.E.M, compared by ANOVA and Bonferroni's Tests, p values <0.05 were considered significant. Results: SIM administration reduced SBP in SHR (SHR-CTL 203 ± 3 vs.SHR+SIM 172 ± 6 mmHg;p < 0.001). Cerebral FCD was reduced in hypertensive rats compared with normotensive rats (SHR-CTL 337 ± 61 vs. WKY-CTL 421 ± 35 capillaries/mm 2 ;p < 0.05). The administration of SIM during 3 days induced a significant increase in cerebral FCD in hypertensive rats (SHR+SIM 530 ± 31 capillaries/ mm 2 ;p < 0.05). Ach induced arteriolar vasodilation in WKY rats (WKY-CTL +6.6 ± 1.2%) but arteriolar vasoconstriction in SHR (SHR-CTL -1.4 ± 1.3 %;p < 0.05); SIM restored Ach-induced arteriolar vasodilation (SHR+SIM +11.5 ± 3.1%;p < 0.05). Microvascular endothelial dysfunction in SHR was associated with a down-regulation of endothelial nitric oxide synthase (eNOS) expression in the brain (SHR-CTL 0.76 ± 0.1 vs. WKY-CTL1.25 ± 0.2 eNOS/GAPDH (AU);p < 0.05). Treatment of SHR with SIM normalized the brain expression of eNOS (SHR+SIM 2.13 ± 0.7 eNOS/GAPDH (AU);p < 0.05). Conclusions: Acute treatment with simvastatin reversed cerebral microvascular rarefaction and restored brain microvascular endothelial function of hypertensive rats. In addition to cholesterol-lowering effects, vascular pleiotropic effects of statins could turn out to be a new therapeutic approach for improving microcirculatory function in hypertensive patients